Knowledge and acceptance of interventions aimed at reducing sugar intake in Portugal - Prada, M. (2020)
Objective: Governments worldwide have been implementing interventions aimed at improving citizens' dietary habits. Examining how individuals perceive these interventions is relevant for promoting future policies in this area, as well as informing the way they are designed and implemented. In the current study, we focused on interventions aimed at reducing sugar intake in Portugal, given the current high sugar consumption patterns in the population. Design: Online survey to assess which interventions are the most salient and receive greater public support. Setting: Portugal. Participants: 1010 (76·7 % female, M Age 36·33, sd 13·22). Results: Data from a free-recall task showed that only about one-third of participants reported knowing about these interventions, namely those related to taxation, weight restrictions in individual sugar packets and limited availability of products with high sugar content. We also found evidence of high support for the eight interventions presented (except for replacing sugar by artificial sweeteners), positive attitudes towards the need of reducing sugar intake in the Portuguese population and high agreement with the importance of reducing sugar intake across all age groups, particularly among children. Participants also indicated paying attention to the amount of sugar in their diets and a low self-reported frequency of consumption of high sugary foods and beverages. A hierarchical regression analysis suggested that these variables were significantly associated with the overall acceptance of interventions, independently of social-demographic variables (i.e., age, education and sex). Conclusion: By examining how people perceive and accept different interventions targeting the reduction of sugar intake, the current work aims to support policymaking in this domain.